2020
DOI: 10.21608/jpd.2020.106550
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Gibberellic Acid and Royal Jelly Injection on Some Productive, Reproductive and Physiological Traits in Matrouh Chickens Strain During Summer Season.

Abstract: A total of 168 laying hens and 21 cocks of Matrouh local strain at 24 weeks of age (At 43.93 % egg production)was used in a completely randomized design among seven treatment groups with three replicates per treatment group (8 hens and 1 cock per replicate).Birds are biweekly injected, up to 36 weeks of age (12 weeks). The 1 st treatment group of birds were injected with saline solution 0.9% only and served as control, The birds in 2 nd and 3 rd treatment groups, were injected subcutaneously with 100 and 200 μ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…While, the lowest value of economical efficiency 89.41 % and 83.44% were recorded in the Ts and control groups, respectively in pullets during at the end of the experimental period (24-48 weeks of age). The same results were obtained by Ezzat et al (2020), result showed that the clearer that Matrouh layers injected with 200 μg of GA 3 /kg BW were recorded the highest net revenue and the best economical efficiency followed by those 100 μg of GA 3 /kg BW as compared with the control groups, while 50 or 100 μg of RJ/kg BW had the lowest net revenue and economical efficiency (%).…”
Section: Economical Efficiency % (Ee)supporting
confidence: 78%
See 3 more Smart Citations
“…While, the lowest value of economical efficiency 89.41 % and 83.44% were recorded in the Ts and control groups, respectively in pullets during at the end of the experimental period (24-48 weeks of age). The same results were obtained by Ezzat et al (2020), result showed that the clearer that Matrouh layers injected with 200 μg of GA 3 /kg BW were recorded the highest net revenue and the best economical efficiency followed by those 100 μg of GA 3 /kg BW as compared with the control groups, while 50 or 100 μg of RJ/kg BW had the lowest net revenue and economical efficiency (%).…”
Section: Economical Efficiency % (Ee)supporting
confidence: 78%
“…Testosterone enhanced survivorship could potentially increase lifetime reproductive success (Daan and Tinbergen 1997;Stearns, 1992). On the other hand, the present results may be related to the active principles of RJ which, is considered to be an excellent food resource as it contains a wide range of biochemical and nutritionally important substances as: minerals, trace elements, wide range of carbohydrates, organic acids, lipids, sterols, nucleic acids, free amino acids, vitamins and over 100 kinds of enzymes and cofactors which increased the immunity of chickens and reduce the mortality rate (Ezzat et al, 2020).…”
Section: Egg Production Traitsmentioning
confidence: 69%
See 2 more Smart Citations
“…Despite some of these substances being considered by-products, they are sources of bioactive compounds with relevant biological effects and significant impacts on animal physiological and productive performance [4,29,30]. Several studies have found that bee products, with a high content of essential amino acids, antioxidants, active enzymes, vitamins, minerals, antibacterial, antiprotozoal, and immunostimulant substances, can improve animals' growth, meat quality, and immunological performance [3,4,[31][32][33][34] (Figure 1). Rabie et al [29] found that administering propolis (400 mg/kg diet) or bee-pollen (2 g/kg diet) to the broiler diets as well as adding bee-venom (2 mg/L water) to broiler drinking water is recommended instead of using antibiotics in broiler farms to increase body weight and improve blood biochemical indices.…”
Section: Propolismentioning
confidence: 99%